THE LINGUODIDACTIC FOUNDATIONS OF PROJECT-BASED TECHNOLOGY AND ITS ROLE IN TEACHING UZBEK AS A FOREIGN LANGUAGE - Omonov Mukhammadaziz Khalimjon o‘g‘li (Modern American Journals, 2025)
This article explores the developmental stages of project-based technology in both foreign and national pedagogical contexts, examines its didactic foundations, and evaluates its linguodidactic potential in teaching Uzbek as a foreign language. The study highlights the historical roots of project methodology, its integration with learner-centered and problem-based learning, its practical orientation, and its role in fostering learner autonomy. Additionally, the article analyzes the project method’s contribution to creativity, motivation, collaboration, and interdisciplinary integration. Particular attention is given to how project-based instruction develops communicative competencies among foreign learners of Uzbek.
Keywords: project-based learning, linguodidactics, Uzbek language, foreign language teaching, learner-centered approach, problem-based learning, communicative competence, innovative pedagogy